Tick Size and Market Quality Using an Agent-Based Multiple-Order-Book Model - Zhao, Ruwei; Cui, Yian; Liu, Xuenu (Frontiers in Physics, 2020)
This study investigated the dynamics between tick size and market quality using an agent-based multiple-order-book stock-market model. Given the multiple-order-book setting, we integrated the model with small-, medium-, and large-cap stocks and conducted the analysis from both a tick-size-series and cross-sectional perspective. The simulation results showed that small-cap stocks were of the lowest quality. Further, quality was generally weakened as tick-size value increased, with expanded bid-ask spreads, elevated market volatility, and reduced market efficiency.